THE EFFECT OF PROJECT-BASED LEARNING ON THE SCIENTIFIC LITERACY OF PROSPECTIVE TEACHER STUDENTS - Agustina, Wilyati; Suhartatik , Suhartatik (Cendikia: Jurnal Pendidikan dan Pengajaran, 2025)
The results of the study show that overall scientific literacy before and after the implementation of project-based learning experienced an increase in scientific literacy which is inseparable from the learning that. applied, namely project-based learning. Project-based learning provides students with the opportunity to explore concepts applied in everyday life or in outside the classroom. This results in more meaningful student understanding because knowledge is integrated with everyday life experiences through collaboration and problem-solving.